Exploring the Effectiveness of BWI's Digital Waqf Campaign: A Netnographic Analysis of Social Media Engagement - Safna, Fadhlurrohman Fakhri; Apriantoro, Muhamad Subhi (Ethica: International Journal of Humanities and Social Science Studies, 2024)
The digital waqf campaign by BWI is to introduce waqf more broadly to the public through social media. This study aims to discuss how BWI campaigns waqf during the COVID-19 pandemic by utilizing digital means. The author uses qualitative methods. Case studies through BWI were conducted to find data in the form of posts. Then the netnography approach was used to analyze 659 posts from BWI: Facebook, Instagram, Twitter, and YouTube. Nvivo12 software analysis is used in performing analytical procedures. The results obtained from this study were that there were five parent nodes, and each parent node pointed to 4 cases from analysis using the Nvivo12 pro application. The five central node nodes are webinars, workshops, talk shows, online "ngaji", and roadshows. This node points to 4 cases: Facebook, Instagram, Twitter, and YouTube. So the result is that BWI carried out a digital waqf campaign during the pandemic using social media in the form of Facebook, Instagram, and YouTube with several activities made by BWI, namely Webinars, Workshop, Talkshows, online studies, and Roadshow.